2002
DOI: 10.1038/sj.bjc.6600329
|View full text |Cite
|
Sign up to set email alerts
|

CD10 is a marker for cycling cells with propensity to apoptosis in childhood ALL

Abstract: CD10 constitutes a favourable prognostic marker for childhood acute lymphoblastic leukaemia. Since correlations between CD10, cell cycle and apoptotic abilities were demonstrated in various cell types, we investigated whether differences existed in the cycling/apoptotic abilities of CD10-positive and CD10-negative B acute lymphoblastic leukaemia cells. Twenty-eight cases of childhood acute lymphoblastic leukaemia (mean age of 6.8 years) were subdivided into two groups according to high (17 cases, 93.2+4.5%, MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 58 publications
(41 reference statements)
2
30
0
3
Order By: Relevance
“…Indeed, data from in vitro studies indicate that the role of bcl6 as promotor or inhibitor of apoptosis or proliferation may depend on the cellular context and the experimental approach (36 -46). In addition, in vitro studies and studies of normal lymphoid tissue and lymphoid malignancies showed that the expression of CD10 protein is associated with apoptosis and proliferation (4,5,10,(47)(48)(49)(50)(51). However, to the best of our knowledge, there is no detailed histological information about the relation of bcl6 and CD10 expression status with apoptosis and proliferation in diffuse large B-cell lymphomas.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Indeed, data from in vitro studies indicate that the role of bcl6 as promotor or inhibitor of apoptosis or proliferation may depend on the cellular context and the experimental approach (36 -46). In addition, in vitro studies and studies of normal lymphoid tissue and lymphoid malignancies showed that the expression of CD10 protein is associated with apoptosis and proliferation (4,5,10,(47)(48)(49)(50)(51). However, to the best of our knowledge, there is no detailed histological information about the relation of bcl6 and CD10 expression status with apoptosis and proliferation in diffuse large B-cell lymphomas.…”
mentioning
confidence: 78%
“…There are several lines of evidence indicating a positive correlation of CD10 expression with proliferation and apoptosis in both normal and malignant B-cells. Indeed, (1) germinal center cells are characterized by high proliferation and have the propensity to undergo apoptosis and upregulate CD10 expression on apoptotic induction, whereas CD10 is absent on other subsets of mature B-cells that are not characterized by high apoptosis (47,48,51), (2) Burkitt's lymphoma cells that are characterized by high proliferation and apoptosis almost constantly express CD10 (4,5,10), and (3) CD10-positive B-acute lymphoblastic leukemia cells were cycling cells with elevated c-myc and propensity to apoptosis, whereas CD10-negative B-acute lymphoblastic leukemia cells had lower cycling capacities and c-myc levels and were resistant to apoptosis (50). Moreover, human postthymic and thymic T-cells express CD10 when undergoing apoptosis (49).…”
Section: Discussionmentioning
confidence: 99%
“…Another low-expressed gene in this group is Max-interacting protein 1 (MXI1), a transcriptional repressor of myc, which is thought to be a tumor suppressor gene. CD10, often considered a marker of better survival in children with pre-B and T-ALL, and recently shown to be characteristic of cycling, apoptosis prone cells, [27][28][29] was expressed at lower levels in the refractory group.…”
Section: Gene Expression Profile Associated With Response To Therapymentioning
confidence: 99%
“…Recently, a somatic mutation in exon 12 of JAK2 has been described in myeloproliferative diseases: Philadelphia chromosome negative as polycythemia vera (PV), essential thrombocythemia (ET) and idiopathic myelofibrosis (IMF), 1 and more recently this mutation has also been investigated in acute myeloid leukemia (AML), myelodysplastic syndrome (MDS), atypical chronic myeloid leukemia (aCML) (BCR-ABL negative), acute lymphoblastic leukemia (ALL) and chronic lymphocytic leukemia (CLL). 2,3 This point mutation results in a substitution of valine for phenylalanine at position 617 (V617F) in the JH2 domain and leads to constitutive tyrosine phosphorylation and cytokine hypersensitivity. Neoplastic cells can be heterozygous for the mutation or hemizygous if they have loss of heterozygosity of 9p chromosome, where JAK2 is located.…”
Section: Screening Of Jak2 V617f Mutation In Multiple Myelomamentioning
confidence: 99%
“…1 The neutral endopeptidase 24.11, (NEP or CD10), is considered a regulator of B-cell growth and proliferation. 2 The enzyme is a cell surface aminopeptidase capable of degrading a number of bioactive peptides with various functions that depend on the cell type or tissue of origin and is active in early bone marrow (BM) precursor B cells and lymph node germinal center (GC) B cells. In addition, CD10 is expressed in malignancies including precursor B cell acute lymphocytic leukemia (B-ALL), GC-related non-Hodgkin's lymphoma (NHL) such as Burkitt's lymphoma and follicular lymphoma (FL), and GC-related diffuse large B-cell lymphomas (DLBCL).…”
mentioning
confidence: 99%